Towards better healthcare quality: meeting the needs of people with disabilities for health services in the Lithuanian Health System - Rupšienė, Liudmila; Batucina, Aleksandra (Family Medicine & Primary Care Review, 2025)
Having undertaken the obligations to the United Nations and the European Union policy in the area of human health, Lithuania is persistently developing its health system, seeking to improve the health and welfare of its citizens, to reduce health inequalities, to enhance public health and to ensure a people-oriented universal, equal, sustainable and high-quality system of health. Despite the efforts, the quality of health services in the country is still assessed as lower than in the OECD countries. Quite a large number of facts and research studies reveal existing problems that people with disabilities face in the health system. Aiming to find out how the Lithuanian health system meets the basic needs of people with disabilities, a survey was carried out in 2019–2020. The survey aimed to investigate how the needs of people with disabilities for health services in the health system are met, revealing links with such characteristics as gender, severity of disability, nature of disability (congenital or acquired), the need for regular care and living conditions. People with disabilities were asked about their needs for emergency medical aid, treatment, palliative care, nursing in nursing hospitals, centers and other health care institutions, as well as at home, and about the need for rehabilitation, psychological support, social support, assessment of disability and capacity for work. The research results showed that, in general, needs were met better than the average. However, differences were expressed in meeting the needs depending on the types and severity of disability, as well as living conditions and the gender of a particular individual. The obtained results point out important aspects, such as that some groups of people with disabilities are faced with some disadvantages in health system performance, and provide preconditions for more purposeful improvement of the system, aiming to meet lawful needs of people with disabilities to obtain qualitative health services and to ensure better quality of life.